READING AS THE BASIS FOR THE FORMATION OF THE SPIRITUAL POTENTIAL OF YOUTH (Web of Teachers: Inderscience Research, 2025)
The article examines the socio-philosophical point of view of the author that the culture of reading, which is considered relevant in society today, is the basis for the formation of youth competence, and also an attempt is made to objectively analyze the role of new information technologies in the development of a reading culture for youth. The importance of libraries is noted. and new information technologies. It is emphasized that the love of reading in Uzbekistan is inherited from our ancestors and the phenomenon of reading is one of the less studied areas. It is concluded that the role of new information technologies as a complex object of research has not been studied, especially the issues of forming a reading culture among young people.